Study of ovine cysticercosis in two slaughterhouses in the north of Algeria - DAHMANI, A; AISSI, M; ZENIA, S; HARHOURA, K; SAADI, A (Journal of the Hellenic Veterinary Medical Society, 2022)
A total of 10696 randomly selected sheep have been collected in two slaughterhouses in the north of Algeria (El Harrach and Boufarik) to determine the prevalence of ovine cysticercosis, to find out the association between prevalence and potential risk factors as well as to assess the distribution of C. tenuicollis and C. ovis in surface’s muscles, viscera and cavities (abdominal, thoracic and pelvic) of slaughtered sheep. Sheep were native breedsand originated from different sub-districts within the municipality and its environs. All the slaughtered sheep carcasses were visually and carefully inspected. Ovine cysticercosis was found in 461 sheep (4.31%). There were Cysticercus tenuicollis and Cysticercus ovis with respectively, 2.25% and 2.06% prevalence. The prevalence of C. ovis was significantly higher (p<0.0001) in females than males while all positive for C. tenuicollissheep were male. The prevalence of the both species increased with age, and the difference was statistically significant (p<0.0001). For C. ovis, it didn’t have significant difference between season, but, the incidence of C. tenuicollis was significantly higher (p<0.0001) in autumn. All the detected cysts of C. ovis were non-viable, and were more frequently detected in the heart (51.82%) followed by diaphragm (30.77%) and esophagus (17.41%). The predominant localization of C. tenuicollis were the liver (57.71%) and the omentum (42.29%), however, no vesicle was observed in the peritoneum. This anatomical distribution of C. ovis and C. tenuicollis cysts showed a significant variation (p<0.001) in different predilection sites. The present study has revealed a non-negligible prevalence of ovine cysticercosis in the two slaughterhouses in the north of Algeria,suggesting that ovine cysticercosisis present in the north of Algeria. Appropriate control measures need to be introduced to reduce the prevalence of these parasites in sheep.